Al-Quran digitalization: adolescent view on the value of the digital AL-Quran application - Mahfudlah Fajrie; Dwi Agung Nugroho Arianto; Yuyun Wahyu Izzati Surya; Akhirul Aminulloh (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study analyses and explains the boundaries between the sacred and profane in digital Al-Quran applications contained in smartphones. This research uses an ethnographic approach. The research study subjects were Muslim teenagers who use digital Al-Quran applications. The results showed a difference in the treatment of Muslim teenagers using digital Al-Quran with the Al-Quran in the form of manuscripts. The existence of a digital Al-Quran makes its sacred value disappear due to the rites, ethics and prohibitions attached to it. In addition, some digital Al-Quran applications bring up advertisements and notifications that interfere with the user's focus on reading them. The development and convergence of the media have made secular values into the Al-Quran and finally eliminated the sacred value of the Al-Quran itself with the loss of the rituals attached to the Al-Quran. The results of this study indicate a novelty, namely that Muslim youth simplify the use of digital Al-Quran applications compared to manuscripts considered more sacred as God's revelation. This shows that modernisation has also bulldozed sacred religious institutions. So, this study criticises the theory of Emil Durkheim and Antony Giddens regarding sacred and profane contexts. Novelty in this research, namely that Muslim youth simplify using digital Al-Quran applications compared to manuscripts considered more sacred as God's revelation. This shows that modernisation has also bulldozed sacred religious institutions. So this study criticises the theory of Emil Durkheim and Antony Giddens regarding sacred and profane contexts.